2023
DOI: 10.1155/2023/6565088
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Low Socioeconomic Background on a Child’s Educational Achievements

Abstract: A child’s educational achievements are based on multiple factors, including their family, their family’s behavior, socioeconomic status, their behavior toward their parents, etc. The main objective of the study is to establish the relationship between the socioeconomic background of the children and their educational achievements and how it impacts their psychology. A descriptive survey research design was used to conduct this study. The target population was 50 students and either of their parents. The target… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(13 citation statements)
references
References 57 publications
(55 reference statements)
0
3
0
Order By: Relevance
“…These challenges include improving poor infrastructure and addressing the shortage of skilled teaching professionals [ 28 ]. Additionally, it is crucial to prioritize the needs of children from poor households, as they are more likely to have migrating parents and caregivers who may have limited education and knowledge about early childhood care [ 29 ]. This study also revealed a correlation between poor ECDI outcomes and children from disadvantaged households, aligning with existing data from LMICs [ 3 , 4 ].…”
Section: Resultsmentioning
confidence: 99%
“…These challenges include improving poor infrastructure and addressing the shortage of skilled teaching professionals [ 28 ]. Additionally, it is crucial to prioritize the needs of children from poor households, as they are more likely to have migrating parents and caregivers who may have limited education and knowledge about early childhood care [ 29 ]. This study also revealed a correlation between poor ECDI outcomes and children from disadvantaged households, aligning with existing data from LMICs [ 3 , 4 ].…”
Section: Resultsmentioning
confidence: 99%
“…Given that the research area is located in the northwest of the country, it is possible that the prevalence of school bullying in this region is influenced by parenting styles and factors such as economic conditions and educational attitudes, which have already been recognized as influential factors [19]. In economically disadvantaged areas, parents often have lower levels of education, and they tend to focus solely on their children's academic achievements while neglecting their psychological well-being [20]. They may not know how to properly guide their children through sensitive psychological phases.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, disparities in socio-economic conditions, parental education levels, and access to resources could play a role [28]. Children who do not participate in early childhood education programs may face additional challenges related to family income, educational support at home, and overall household well-being [21,[29][30][31]. Addressing these socio-economic determinants becomes crucial in understanding and mitigating the negative effects observed in ECDI outcomes.…”
Section: Discussionmentioning
confidence: 99%